The Minnesota Multi‐Investigator 2012 Presidential Election Panel Study. Issue 1 (20th January 2014) - Chen, Philip G.; Appleby, Jacob; Borgida, Eugene; Callaghan, Timothy H.; Ekstrom, Pierce; Farhart, Christina E.; Housholder, Elizabeth; Kim, Hannah; Ksiazkiewicz, Aleksander; Lavine, Howard; Luttig, Matthew D.; Mohanty, Ruchika; et al.
<x xml:space="preserve">Abstract</x> In an analysis of the 2012 presidential election, we sought to optimize two key desiderata in capturing campaign effects: establishing causality and measuring dynamic (i.e., intraindividual) change over time. We first report the results of three survey‐experiments embedded within a three‐wave survey panel design. Each experiment was focused on a substantive area of electoral concern. Our results suggest, among other findings, that retrospective evaluations exerted a stronger influence on vote choice in the referendum (vs. the choice) frame; that among White respondents, racial animosity strongly predicted economic evaluations for knowledgeable Republicans who were led to believe that positive economic developments were the result of actions taken by the Obama administration; and that information‐seeking bias is a contingent phenomenon, one depending jointly on the opportunity and motivation to selectively tune in to congenial information. Lastly, we demonstrate how the panel design also allowed us to (1) examine the reliability and stability of a variety of election‐related implicit attitudes, and to assess their impact on candidate evaluation; and (2) determine the causal impact of perceptions of candidates' traits and respondents' policy preferences on electoral preferences, and vice versa, an area of research long plagued by concerns about endogeneity.